Trigeminal somatosensation in the temporomandibular joint and associated disorders - Perry, Sienna K.; Emrick, Joshua J. (Frontiers in Pain Research, 2024)
The temporomandibular joint (TMJ) consists of bone, cartilage, ligaments, and associated masticatory muscles and tendons that coordinate to enable mastication in mammals. The TMJ is innervated by the trigeminal nerve (CNV), containing axons of motor and somatosensory neurons. Somatosensation includes touch, temperature, proprioception, and pain that enables mammals to recognize and react to stimuli for survival. The somatosensory innervation of the TMJ remains poorly defined. Disorders of the TMJ (TMD) are of diverse etiology and presentation. Some known symptoms associated with TMD include facial, shoulder, or neck pain, jaw popping or clicking, headaches, toothaches, and tinnitus. Acute or chronic pain in TMD stems from the activation of somatosensory nociceptors. Treatment of TMD may involve over- the-counter and prescription medication, nonsurgical treatments, and surgical treatments. In many cases, treatment achieves only a temporary relief of symptoms including pain. We suggest that defining the sensory innervation of the temporomandibular joint and its associated tissues with a specific focus on the contribution of peripheral innervation to the development of chronic pain could provide insights into the origins of joint pain and facilitate the development of improved analgesics and treatments for TMD.